Art and dissensus : a thesis presented in partial fulfilment of the requirements for the degree of Master of Fine Art at Massey University, Wellington, New Zealand - Ting, Michael Arthur (Massey University, 2010)
For a contemporary art practice, what does it mean to resist? This essay will discuss the idea of resistance in the present day using the work of Karl Marx as the key starting point. If he is foundational to the understanding of capitalism, then later philosophers such as Frederic Jameson and Jacques Ranciere have added considerably to the relevance of Marx, and added their own critical engagement with the art world. Ranciere advocates dissensus, which he sees as being counter to the conformity that liberalism and concensus bring. Political philosopher Chantal Mouffe also advocates dissensus, replacing antagonism with the idea of agonism. There is disagreement but as in sport both parties recognize the legitimacy of their opponent. This is why identity is so important to democracy, for without difference there is no real choice, and so the nature of identity and the subject become crucial factors in conceiving of a way to resist, and a way of being as an artist.
Keywords: Resistance in art; Dissension; Fields of Research::410000 The Arts::410200 Visual Arts and Crafts Studies